Legal Protection for Children in Polygamous Families in View from Law Number 1 of 1974 in Bandung Regency - Muchtarom, Muchtarom (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The research objective to be achieved is to determine the implementation of legal protection for children in polygamous families. To determine the factors inhibiting the implementation of legal protection for children. To find out efforts to overcome the obstacles that occur. The research method uses qualitative methods that describe phenomena occurring at the research location. Data collection techniques include in-depth interviews, observation, and documentation studies. Conclusions on the implementation of legal protection for children of polygamous families in Bandung Regency. Because it has not been implemented very well, Factors that hinder the implementation of legal protection for children in polygamous families and efforts to overcome obstacles faced by families who practice polygamy. To find additional work for the wife, the children who can work help their father.